Half of children with IgA vasculitis‐associated nephritis with nephrotic state spontaneously recover. Issue 8 (9th April 2022) - Deki, Saori; Hamada, Riku; Mikami, Naoaki; Terano, Chikako; Harada, Ryoko; Hamasaki, Yuko; Ishikura, Kenji; Honda, Masataka; Hataya, Hiroshi
Abstract: Background: The clinical spectrum of Henoch–Schönlein purpura nephritis (HSPN), now known as IgA vasculitis‐associated nephritis (IgAVN), ranges from isolated microscopic haematuria to nephrotic syndrome, progressive glomerulonephritis, and kidney failure. The outcome also varies, and the management of IgAVN is controversial. The presence of nephrotic state at disease onset is thought to be a risk factor of a poor prognosis. However, not all patients with nephrotic state have a poor prognosis, and it is unclear whether they need early treatment. Methods: We herein retrospectively examined the clinical course of paediatric IgAVN cases with nephrotic state (serum albumin [sAlb]<3.0 g/dL and urine protein–creatinine ratio of >2.0 g/ gCr) without kidney injury treated at our hospital between 2010 and 2018. Results: Of the 216 patients with IgAVN identified, 17 met the inclusion criteria. The median follow‐up period from disease onset to the last observation was 40.5 months (IQR:31.0–74.2). Eleven patients were male, the median age at onset was 5 years, the minimum serum Alb level was 1.9 g/dL, the maximum proteinuria value was 12.3 g/gCr, and the median minimum eGFR was 86.0 mL/min/1.73 m 2 in the acute phase. Eight patients (47%) achieved resolution of nephrotic state within 3 months and complete remission without treatment by the last observation. The patients with spontaneous resolution of nephrotic state had less severe hypoalbuminaemia (Alb<2.0 g/dL) and tended to show a quick increase in the serum albumin level. Conclusions: Our study found that half of paediatric patients with IgAVN with nephrotic state achieved spontaneous resolution without treatment and enjoyed a favourable short‐term outcome. Consideration of the duration of nephrotic state and trends in the serum albumin level in children with IgAVN may allow unnecessary kidney biopsies and immunosuppressive therapy to be avoided. SUMMARY AT A GLANCE: In this retrospective study, eight patients (47%) out of 17 paediatric IgA vasculitis‐associated nephritis with nephrotic state achieved spontaneous resolution without treatment and enjoyed a favourable short‐term outcome.